The bridge between ontological concepts and empirical evidence: an interview with Rob Stones. Issue 7 (19th September 2016) - Stones, Rob; Jack, Lisa
Abstract : Purpose: The purpose of this paper is to share interdisciplinary ideas about the purpose of social theory in empirical research. Design/methodology/approach: The formal interview took place in front of an audience at the Strong Structuration Theory and Management Research workshop at IAE de Paris, Université Paris I Panthéon-Sorbonne, on 10 May 2016. A recording was made, transcribed, and then edited. Elements from a recorded lecture on the same day are also included. A conversational format is retained to enhance the sense of interdisciplinary dialogue that characterises the research project. Findings: The use of SST as a conceptual methodology is explained, and the use of agent's conduct and agent's context analyses is elucidated providing pointers regarding how accounting research can be developed further by basing the analysis in an understanding of the status and adequacy of knowledge on which people act to produce and reproduce structure. Originality/value: The value of the interview is to provide insights into the process of empirical research and conceptualisation, which are likely to be particularly helpful for early career researchers.